2022
DOI: 10.3389/fspor.2022.898720
|View full text |Cite
|
Sign up to set email alerts
|

Daily Fluid Intake Behaviors and Associated Health Effects Among Australian and United States Populations

Abstract: Minimal data exist exploring intercontinental differences in fluid intake (FI) beliefs and behaviors and the impact on fluid intake practices (i.e., fluid intake volume, beverage type, and timing of fluid intake). Therefore, this study explored the impact that FI beliefs and behaviors had on FI practices among emerging adults living in the United States (USA) and Australia (AUS). A total of 489 individuals (74.5% female; USA, 79.4%; age, 25 ± 6 years completed a 23-item survey between November 2020 and June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…The current study revealed that females consumed less SSBs, particularly sweetened tea and coffee, than males. Our results are consistent with those of previous population-based studies [ 49 , 50 ]. Another study reported that females consumed SSBs on most days or daily; however, additional details were not provided [ 51 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The current study revealed that females consumed less SSBs, particularly sweetened tea and coffee, than males. Our results are consistent with those of previous population-based studies [ 49 , 50 ]. Another study reported that females consumed SSBs on most days or daily; however, additional details were not provided [ 51 ].…”
Section: Discussionsupporting
confidence: 94%
“…Total water intake can facilitate regular eating and ME. In a cross-cultural study, Sims et al reported that the mean daily water intake of Australians and Americans was 1796 and 1535 mL, respectively [ 49 ]. They noted that drinking 0.9 L of water daily affected all IE subscales, ED, and MF; however, no effects were observed on total ME.…”
Section: Discussionmentioning
confidence: 99%
“…We also cannot discount the potential influence of our sample’s pre-pandemic fluid intake behaviors in that our sample may have been habitually under consuming fluids. However, our previous work disputes the low prevalence of college students meeting fluid intake recommendations [ 57 , 58 ]. In addition to females exhibiting a lower total fluid intake than males, our study also found that females consumed less total fluid, beer, hard liquor, coffee, energy drinks, milk, and soft drinks than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 2% hypohydration is defined as a water deficit equal to 2% of body mass. Surprisingly, hypohydration prevalence is high among adolescent and other populations. ,, , For instance, a high prevalence of hypohydration, measured by urine specific gravity level, was reported in summer and winter, 94% to 72%, respectively.…”
mentioning
confidence: 99%
“…It is critical to know that hydration status differs from one person to another. There are many cases in which participants were not hydrated enough but were healthy otherwise. , Hydration status, even in healthy people, is a function of daily fluid intake, , longitudinal hydration, daily activity, amount of coffee consumption, pretrial body mass index and degree of obesity, exercise, its severity and duration, weight loss and speed of weight loss or the degree of weight loss, amount and type of protein/meat consumption, and salt consumption behavior, just to mention a few. For instance, it has been shown that, while young adults with higher salt intake had higher total drinking fluids, total water intake, and water from food, counterintuitively, this group had inferior hydration status, suggesting that a reduction in salt intake among young adults helps to keep optimal hydration status …”
mentioning
confidence: 99%